Increasing Sales of Pertamina Non-PSO Fuel Through New Concept of Gas Station - Pirous, Haekal; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2013)
Pertamina must increase revenues from the sale of Non- Public Service Obligation (PSO) Fuel. Increased sales of Non-PSO fuel Pertamina can be obtained if Pertamina can give right market offering to the general market segment â€œBBM Non-PSO and PSO Combinerâ€. Research showed that Pertamina gas station CVP is under CVP competitors so lowering costumer experience and the business ecosystem of Pertamina also have problem. Based on that data, researchers proposed a new concept of gas station that only sell Non-Pso fuel named Pertamina Prime-X Gas Station and have new business ecosystem. Â Keyword: Costumer Value Proposition, Business Ecosystem.Â